Analysis of the Interrelationship of the Technical-Tactical Indicators of the Wrestlers (Texas Journal of Multidisciplinary Studies, 2022)
This article examines the interrelationship of technical and tactical indicators of wrestlers. Recommendations for the development of technical and tactical indicators and the introduction of effective innovative approaches have been developed.